The effect of Concrete Roof Tile Composite (CRTC) using Sayong clay and rice straw fibre on the flexural strength / An Nisha Nur Welliana Abd Rased and Nurhidayah Samsul Rijal - Abd Rased, An Nisha Nur Welliana; Samsul Rijal, Nurhidayah (2021)
The flexural strength of CRTC composite when combined with rice straw fibre (RSF) and clay was analyzed in this research. The clay was sourced from Sayong Kuala Kangsar, Perak in Malaysia while the rice straw fibre was collected from Kuala Kurau, Perak in Malaysia. Different percentage of clay (10%, 20% and 30%), different percentage of rice straw (1.0%,1.5% and 2.0%) and different length of rice straw (0.1-2.0cm, 2.1-4.0cm and 4.1-6.0cm) were added to a mix ratio 1: 2 for cement and sand to produce concrete roof tile composite plates. The result showed that the rise in the percentage of rice straw increased the flexural strength continuously until 5.51N/mm² for the 2.0% of rice straw tested in 300 days whereas the increase of clay percentage and length of rice straw decreased the flexural strength of concrete.